Rehash of cooked oil for the palatable water production using single slope solar still. (1st July 2020) - Balachandran, Gurukarthik Babu; David, Prince Winston; Chellam, Padmanaban Velayudhaperumal; Ali, Mohamed Nasrulla Akbar; Radhakrishnan, Vignesh; Balamurugan, Ramkumar; Manokar, A. Muthu
Abstract: The present work investigates about the performance of single slope still (with rehash cooked oil) to enhance the palatable water productivity. The tray with basin contains rehash cooked oil represent the external heat source to increase the temperature of basin water. The performance of proposed solar still with the effects of high heat exchanger rehash cooked oil are studied. In this study, the proposed solar still is compared with conventional solar still for the purpose of evaluating the palatable water productivity under the presence of same ambient condition. The experimental result is obtained during the period from March to May 2019 under the Indian conditions. The production of palatable water reached 3.77 L\m 2 for the proposed still, while it is only 3.02 L/m 2 for the conventional still. The rate of rise of yield obtained from the single slope solar still with used cooked oil is 57.02% more than the yield obtained from the conventional still in an average. For the proposed still, the energy efficiency is 24.35% and the exergy efficiency is 0.69%.